2022
DOI: 10.3390/antiox11061063
|View full text |Cite
|
Sign up to set email alerts
|

Silicon- and Boron-Induced Physio-Biochemical Alteration and Organic Acid Regulation Mitigates Aluminum Phytotoxicity in Date Palm Seedlings

Abstract: The current study aimed to understand the synergistic impacts of silicon (Si; 1.0 mM) and boron (B; 10 µM) application on modulating physio-molecular responses of date palm to mitigate aluminum (Al3+; 2.0 mM) toxicity. Results revealed that compared to sole Si and B treatments, a combined application significantly improved plant growth, biomass, and photosynthetic pigments during Al toxicity. Interestingly, Si and B resulted in significantly higher exudation of organic acid (malic acids, citric acids, and acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
2
7
0
Order By: Relevance
“…B, Si, and their combination can activate APX, CAT, and POD, which are the antioxidant enzymes responsible for scavenging H 2 O 2 under Al stress ( Figure 4 A–C). Consistent with our findings, Pontigo et al observed that Si significantly reduced lipid peroxidation induced by Al toxicity, and similarly, B application reduced oxidative damage to plants subjected to Al stress [ 42 , 45 , 46 ]. In summary, supplementation with B, Si, and their combination mitigated oxidative damage by reducing the accumulation of ROS and MAD and triggering the up-regulation of the antioxidant system ( Figure 3 and Figure 4 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…B, Si, and their combination can activate APX, CAT, and POD, which are the antioxidant enzymes responsible for scavenging H 2 O 2 under Al stress ( Figure 4 A–C). Consistent with our findings, Pontigo et al observed that Si significantly reduced lipid peroxidation induced by Al toxicity, and similarly, B application reduced oxidative damage to plants subjected to Al stress [ 42 , 45 , 46 ]. In summary, supplementation with B, Si, and their combination mitigated oxidative damage by reducing the accumulation of ROS and MAD and triggering the up-regulation of the antioxidant system ( Figure 3 and Figure 4 ).…”
Section: Discussionsupporting
confidence: 92%
“…This study revealed the inhibited root growth potential and parameters under Al toxicity (50 μM Al) ( Figure 1 ). Several mechanisms have been proposed for plant resistance to aluminum toxicity, and it has become evident that B and Si play an indispensable role in plant tolerance to aluminum toxicity [ 42 ]. In our current study, the B + Si combination and B and Si alone significantly reversed the root growth inhibition induced by Al toxicity ( Figure 1 C), which is consistent with earlier reports in citrus and date palm seedlings [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(Cakmak and Horst, 1991). In a study of date palm seedlings under Al stress, the boron treatment reduced MDA and superoxide production levels (Bilal et al, 2022). Our results show that whether the germinated buckwheat or the buckwheat in the seedling stage, Al stress signi cantly increased MDA content in roots as well as leaves (Fig.…”
Section: Effects Of Boron On Antioxidant Enzyme System Under Al Stresssupporting
confidence: 50%